Knowledge mapping and trend analysis of disaster mitigation research in the Sulawesi Islands of Indonesia: a bibliometric study using VOSviewer - Muhammad Ahsan Samad; Kadir Arifin; Azlan Abas; Tiwi Eka Sari (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indonesia, as an archipelagic country located on the Pacific Ring of Fire, faces a high risk of natural disasters, including earthquakes, tsunamis and volcanic eruptions. Sulawesi Island, which frequently experiences disasters, is the focus of this research to analyze trends and map knowledge related to disaster mitigation. The aim of this research is to highlight the effectiveness of existing mitigation strategies and identify areas that require further attention. The method used is bibliometric analysis with VOSviewer software, using Publish or Perish 8, of key terms in scientific literature. Data includes articles published between 2019 and 2024, with strict inclusion criteria to ensure relevance to disaster mitigation in Sulawesi. Research findings show that the four main types of disasters are floods, landslides, volcanic eruptions and tsunamis. disaster mitigation in Sulawesi. In addition, there is a lack of knowledge and implementation of sustainable mitigation strategies, as well as the need for active involvement of local communities in mitigation programs. The implications of this research emphasize the importance of evaluating existing disaster mitigation programs and more effective development policies, which can increase community preparedness and resilience to disasters. It is hoped that this research can make a significant contribution to efforts to reduce disaster risk in the region, as well as encourage collaboration between government, institutions and society in improving disaster mitigation.